Investigating the impact of surgical masks on behavioral reactions to facial emotions in the COVID-19 era - Montalti, Martina; Mirabella, Giovanni (Frontiers in Psychology, 2024)
The widespread use of surgical masks during the COVID-19 pandemic has posed challenges in interpreting facial emotions. As the mouth is known to play a crucial role in decoding emotional expressions, its covering is likely to affect this process. Recent evidence suggests that facial expressions impact behavioral responses only when their emotional content is relevant to subjects’ goals. Thus, this study investigates whether and how masked emotional faces alter such a phenomenon. Forty participants completed two reaching versions of the Go/No-go task in a counterbalanced fashion. In the Emotional Discrimination Task (EDT), participants were required to respond to angry, fearful, or happy expressions by performing a reaching movement and withholding it when a neutral face was presented. In the Gender Discrimination Task (GDT), the same images were shown, but participants had to respond according to the poser’s gender. The face stimuli were presented in two conditions: covered by a surgical mask (masked) or without any covering (unmasked). Consistent with previous studies, valence influenced behavioral control in the EDT but not in the GDT. Nevertheless, responses to facial emotions in the EDT exhibited significant differences between unmasked and masked conditions. In the former, angry expressions led to a slowdown in participants' responses. Conversely, in the masked condition, behavioral reactions were impacted by fearful and, to a greater extent, by happy expressions. Responses to fearful faces were slower, and those to happy faces exhibited increased variability in the masked condition compared to the unmasked condition. Furthermore, response accuracy to masked happy faces dramatically declined compared to the unmasked condition and other masked emotions. In sum, our findings indicate that surgical masks disrupt reactions to emotional expressions, leading people to react less accurately and with heightened variability to happy expressions, provided that the emotional dimension is relevant to people's goals.